Development of biscuits with green banana flour irradiated by 60Co: Preservation in modified atmosphere packaging - Alvarenga, Nuno (2019)
Banana it’s one of the most consumed fruits in the world but 20% of the production is wasted, mostly due to post-harvest losses, or because it doesn ́t fit in consumers standards. Nonetheless, Green Banana Flour (GBF) can be an alternative to minimize these losses, further being a good source of nutrients, fiber, resistant starch and micronutrients. Considering the interesting possibilities of GBF utilization in the agrofood sector, the aims of this study, was the development of GBF cookies and preservation during three months in two different types of modified atmosphere. The experimental design considered GBF radiation with gamma radiation (1 kGy and 3 kGy), with additional packaging in modified atmosphere, using 100% CO2 or a gas mixture containing 2% O2; 88% N2 e 10% CO2. As a control, non-radiated GBF was used. In general, it was observed that samples submitted to 3 kGy radiation, had the best results. Besides, packaging with gases mixture showed higher efficiency for GBF cookies preservation, due to CO2.